A Team-Based Collaborative Care Model for Youth With Attention-Deficit Hyperactivity Disorder in Education and Health Care Settings. (March 2021) - Talbott, Elizabeth; De Los Reyes, Andres; Power, Thomas J.; Michel, Jeremy J.; Racz, Sarah Jensen
Attention-deficit hyperactivity disorder (ADHD) is among the most commonly diagnosed disorders of children and youth. Young people receive their ADHD diagnoses and medical treatment in primary health care settings and can experience a range of behavioral and educational disabilities treated in the clinic, at home, and at school. We propose a team-based collaborative care model (TBCCM) to foster communication and collaboration among health care and education teams, embedding implementation science methods to promote and sustain evidence-based practices for youth with ADHD. Key features of the model include (a) effective leadership and teamwork within the two universal systems of education and health care, (b) use of data from multiple informants who describe and monitor student behavior within and across contexts, and (c) adoption and adaptation of evidence-based practices. We expect that these efforts to embed implementation science methods within a collaborative team structure will improve the uptake of evidence by intervention teams in the two systems, and thus optimize outcomes for children and youth with ADHD.